Determinants of Audit Delay in Banking Companies on the Indonesia Stock Exchange - Muhammad Adam Rizky Putra; Wahidahwati (Indonesian Scientific Publication, 2026)
This research is designed to evaluate the specific factors driving audit delays within banking institutions traded on the Indonesia Stock Exchange (IDX) from 2020 to 2024. In this context, audit delay represents the duration separating the close of the fiscal year from the signing date of the independent auditor's report, acting as a key metric for financial disclosure punctuality. Promptly published statements remain critical for stakeholder investment evaluations, particularly given the strict compliance requirements of the financial services industry. This study examines the effect of the Debt-to-Equity Ratio (DER), Public Accounting Firm (KAP) size, client business complexity, Dividend Payout Ratio (DPR), and operating cash flow on audit delay. This study employed a quantitative approach using logistic regression analysis and purposive sampling techniques. The data used were secondary data in the form of annual financial reports from 40 selected banking companies, resulting in 230 total observations. The results of the study indicate that DER has a positive and significant effect on audit delay, while DPR has a negative and significant effect. Meanwhile, the size of the accounting firm, the complexity of the client's business, and operating cash flow do not significantly affect audit delay. These findings indicate that leverage level and dividend policy are the main factors influencing the timeliness of audit completion in banking companies.